Catalytic divergent synthesis of imidazoles via reaction condition-dependent [3 + 2] cyclization of TosMIC. Issue 44 (31st October 2022) - Zhao, Cheng; Gu, Man-Zhen; Chen, Yi-Yuan; Hu, Xiao-Wei; Xu, Yi-Bing; Lin, Xiao-Min; Liu, Xin-Ni; Chen, Long; Chen, Guo-Shu; Liu, Yun-Lin
Abstract : A base-catalyzed divergent synthesis of 1, 4, 5-trisubstituted or 1, 4-disubstituted imidazoles through TosMIC-based [3 + 2] cyclization reaction has been developed. Abstract : A base-catalyzed divergent synthesis of multisubstituted imidazoles through TosMIC-based [3 + 2] cyclization reaction has been developed. In the presence of ketenimines and t BuONa, 1, 4, 5-trisubstituted imidazoles were obtained. Nonetheless, in the absence of ketenimines, 1, 4-disubstituted imidazole was produced through cyclodimerization of TosMIC.